MEMBANGUN DIMENSI BARU DAKWAH ISLAM : Dari Dakwah Tekstual menuju Dakwah Kontekstual - Amri Syarif Hidayat (Jurnal Dakwah Risalah, 2013)
This paper will discuss the urgency of developing a new dimension’s of Islamic Communication (dakwah) from textual toward contextual approaches. Textual dakwah tend to give material for granted regardless of whether they need it or not, or even may be already know because often hear. Contextual approach emphasizes seeking to answer the needs of the community. Problems faced by the people not only can be solved just by hearing a lecture course but need real action more concrete. In the modern era where information technology has become part of the life of modern society, it is necessary to adjust a way of dakwah. Methods of socialization and internalization of the Islamic teachings should always be discussed in depth in order to be more effective. It is not only limited to textual approach but should use the technology as a mean of dakwah. It is because that among of the characteristics of modern society is the openess to new experience and believing in science and technology. So, ICT for modern society has become a part of their daily life. In this way, The faculties of Dakwah in the future is expected to play the mayor role.